2012
DOI: 10.1007/s10875-012-9836-3
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils Induce Airway Smooth Muscle Cell Proliferation

Abstract: Asthma is characterized by eosinophilic airway inflammation and remodeling of the airway wall. Features of airway remodeling include increased airway smooth muscle (ASM) mass. However, little is known about the interaction between inflammatory eosinophils and ASM cells. In this study, we investigated the effect of eosinophils on ASM cell proliferation. Eosinophils were isolated from peripheral blood of mild asthmatics and non-asthmatic subjects and co-cultured with human primary ASM cells. ASM proliferation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 51 publications
1
37
0
1
Order By: Relevance
“…Halwani et al (2013) verified that preventing eosinophil contact with ASM cells using specific antibodies or blocking cysteinyl leukotrienes derived from eosinophils was associated with inhibition of ASM proliferation. Moreover, ASM-synthesized cytokines seem to direct the eosinophil differentiation and maturation from progenitor cells, which can promote perpetuation of eosinophilic inflammation and consequently the tissue remodeling in asthma (Fanat et al, 2009).…”
Section: Airway Smooth Musclementioning
confidence: 71%
“…Halwani et al (2013) verified that preventing eosinophil contact with ASM cells using specific antibodies or blocking cysteinyl leukotrienes derived from eosinophils was associated with inhibition of ASM proliferation. Moreover, ASM-synthesized cytokines seem to direct the eosinophil differentiation and maturation from progenitor cells, which can promote perpetuation of eosinophilic inflammation and consequently the tissue remodeling in asthma (Fanat et al, 2009).…”
Section: Airway Smooth Musclementioning
confidence: 71%
“…Our results demonstrate ECM protein production by ASM cells after exposure to eosinophils from asthma and control groups in vitro . However, Halwani et al (2013) suggested that ASM cells proliferation increase irrespective of ECM proteins production in asthma and presume that eosinophils enhance ASM proliferation via the release of CysLTs.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophils isolated from asthmatics, when cocultured with ASM cells, promote enhanced ASM proliferation, which is inhibited by the addition of the leukotriene antagonist montelukast (117). It appears that eosinophils and ASM enjoy a reciprocal relationship, as ASM cells are also known to produce pro-eosinophil cytokines (118).…”
Section: The Eosinophil’s Role In Asthma Pathophysiologymentioning
confidence: 99%